2016
DOI: 10.1504/ijbd.2016.075455
|View full text |Cite
|
Sign up to set email alerts
|

Modelling volatility in Indian currency market

Abstract: Abstract:The present paper aims at studying the relationship between volatility in the exchange rate in the spot market and trading activity in the currency futures market. The data used in this paper comprises of daily exchange rate of USD in terms of Indian rupees for the sample period 1 January 2006 to 12 September 2011. The volatility of the exchange rates has been measured by applying suitable GARCH model. For establishing the feedback causality between the volatility in the spot exchange rate and trading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…This is consistent with other studies' findings that TGARCH and PARCH are the best models for describing asymmetric volatility. (Banumathy & Azhagaiah, 2015), (Goudarzi & Ramanarayanan, 2010), (Mittal, Arora, & Goyal, 2012). The study also found that bad news (bad shocks) have a greater effect on the volatility of DFMGI returns than good news (positive shocks).…”
Section: Discussionmentioning
confidence: 70%
“…This is consistent with other studies' findings that TGARCH and PARCH are the best models for describing asymmetric volatility. (Banumathy & Azhagaiah, 2015), (Goudarzi & Ramanarayanan, 2010), (Mittal, Arora, & Goyal, 2012). The study also found that bad news (bad shocks) have a greater effect on the volatility of DFMGI returns than good news (positive shocks).…”
Section: Discussionmentioning
confidence: 70%
“…It was found that the futures market come out as the leading market (Kharbanda and Singh, 2017). In a study, a bidirectional causal association was also found between volume and returns (Mittal and Kumar, 2016). Similarly, in a study effect of currency derivatives on foreign exchange rate volatility of Pound sterling was examined and it was found that trading of currency futures in India has reduced the foreign exchange rate volatility.…”
Section: Currency Futuresmentioning
confidence: 96%
“…Large number of researches (Karolyi, 1995;Hong, 2001;Koopman et al, 2005;Hammoudeh and Li, 2008;Khemiri, 2011;Bonilla and Sepulveda, 2011;Fiszeder and Orzeszko, 2012;Salma, 2015;Mittal and Kumar, 2016;Demirer, Gupta and Wong, 2019) adopted non-linear ARCH/GARCH family models (Engle, 1982;Bollerslev, 1986) for probing precariousness of different types of time series data. The literature further state that predominance of the research studies in Asia have implemented vector autoregression (VAR) framework, Cointegration and Granger causality test only (Joshi, 2011;Tuan et al, 2015).…”
Section: Review Of Literaturementioning
confidence: 99%